Body Size Measures, Hemostatic and Inflammatory Markers and Risk of Venous Thrombosis: the Longitudinal Investigation of Thromboembolism Etiology - Cushman, Mary (Thromb Res, 2016)
OBJECTIVE: Obesity is an important venous thrombosis (VT) risk factor but the reasons for this are unclear. MATERIALS AND METHODS: In a cohort of 20,914 individuals aged 45 and older without prior VT, we calculated the relative risk (RR) of VT over 12.6 years follow-up according to baseline body size measures, and studied whether associations were mediated by biomarkers of hemostasis and inflammation that are related to adiposity. RESULTS: Greater levels of all body size measures (weight, height, waist, hip circumference, calf circumference, body-mass index, waist-hip ratio, fat mass and fat-free mass) were associated with increased risk of VT, with 4(th) versus 1(st) quartile RRs of 1.5–3.0. There were no multiplicative interactions of biomarkers with obesity status. Adjustment for biomarkers associated with VT risk (factor VIII, von Willebrand factor, partial thromboplastin time, D-dimer and factor XI) only marginally lowered, or did not impact, the RRs associated with body size measures. CONCLUSIONS: Greater body size, by multiple measures, is a risk factor for VT. Associations were not mediated by circulating levels of studied biomarkers suggesting that body size relates to VT because of physical factors associated with blood flow, not the hypercoagulability or inflammation associated with adiposity.